2007
DOI: 10.1021/jp0708805
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Absorption Investigation of the Formation of Cobalt Ferrite Nanoparticles in an Aerogel Silica Matrix

Abstract: X-ray absorption fine structure (EXAFS) and X-ray absorption near-edge structure (XANES) techniques at both Fe and Co K-edges were used to investigate the formation of CoFe 2 O 4 nanoparticles embedded in a silica aerogel matrix as a function of calcination temperature and CoFe 2 O 4 content. In particular, nanocomposite aerogels containing relative CoFe 2 O 4 amounts of 5 and 10 wt % and calcined at 450, 750, and 900°C were studied. The evolution of the nanophase with calcination temperatures depends on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
45
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 46 publications
16
45
1
Order By: Relevance
“…For the bulk standards and two concentration extremes ͑0.3 and 9.0 at. 27,28 For the low-concentration, unannealed samples, the XANES spectrum is similar to that of Co 3 O 4 , including the shift to higher energy, as consistent with Fukimi 29 and Cattaruzza et al, 30 who reported that Co atoms in an as-implanted/as-deposited, NP-free state prefer a tetrahedral arrangement in SiO 2 similar to that in Co 3 O 4 . 5, while the fcc, hcp, and oxide fractions are shown in Fig.…”
Section: Resultssupporting
confidence: 77%
“…For the bulk standards and two concentration extremes ͑0.3 and 9.0 at. 27,28 For the low-concentration, unannealed samples, the XANES spectrum is similar to that of Co 3 O 4 , including the shift to higher energy, as consistent with Fukimi 29 and Cattaruzza et al, 30 who reported that Co atoms in an as-implanted/as-deposited, NP-free state prefer a tetrahedral arrangement in SiO 2 similar to that in Co 3 O 4 . 5, while the fcc, hcp, and oxide fractions are shown in Fig.…”
Section: Resultssupporting
confidence: 77%
“…7(a,b). The determined Co-O distance of 1.98Å is intermediate between the Co-O distances expected for a partially inverted spinel (with distances of 1.89-1.92 and 2.06-2.07Å for tetrahedral and octahedral sites, respectively) [97,98]. The Co-metal second-neighbor shell distance of 2.96Å is in good agreement with the 2.95Å reported by Carta and coworkers [97].…”
Section: Amorphous Cobalt Ferritesupporting
confidence: 83%
“…Furthermore, Nilsen et al [103] measured EXAFS on nanoparticulate CoFe 2 O 4 grown hydrothermally and observed Co-O distances of 2.02(1) and 2.05(7)Å in samples with particle sizes of 16 and 39 nm, respectively. The difference between the Fe-O and Co-O distances in the amorphous samples are representative of the difference in ionic radii for the two elements [104], and comparable to the Fe-O and Co-O distances determined by EXAFS for octahedral sites in CoFe 2 O 4 [97]. Hence, it is not unreasonable to conclude that the amorphous result is consistent with the inverse spinel structure.…”
Section: Amorphous Cobalt Ferritesupporting
confidence: 67%
“…42 A very weak pre-edge peak was observed for CoO due to its octahedral coordination environment 43,44 for cobalt atoms in the first shell. For cobalt, XANES spectra typically show a more distinct pre-edge where Co is present in tetrahedral (T d ) environments, whereas in the case of octahedral (O h ) coordination the pre-edge is less prominent.…”
Section: Materials Characterizationmentioning
confidence: 99%